Studies in Application of Linguistic Ontology Knowledge for Treatment of Dyslexia - Yanqing MA; Zhuoming CHEN; Jiajian YAN (康复学报)
This paper applys the linguistic ontology knowledge in speech therapy for aphasia, and discusses its effect in the treatment of dyslexia. Through teaching experiment follow-up survey, we treated dyslexia of Chinese aphasia by using the theory of word frequency of linguistics, combining the characteristics of Chinese including pictogram, combined ideogrampictogram, ideogram and ideogram plus phonetic. Using ontology knowledge of linguistics and the characteristics of Chinese characters itself can effectively help the aphasia patients to overcome dyslexia.